THE EFFECT OF LISTEN-READ-DISCUSS (LRD) STRATEGY ON READING COMPREHENSION OF THE SECOND YEAR STUDENTS AT SMK DAR EL HIKMAH PEKANBARU - Devi Lusiani; Rumiri Aruan; Jismulatif (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was aimed to find out the significant effect of Listen-Read-Discuss (LRD) strategy on reading comprehension of the second year students at SMK Dar El Hikmah Pekanbaru. This research was pre-experimental with one group pre-test post-test design. The population of this research was the second year students of SMK Dar El Hikmah Pekanbaru. All of the population were taken as the samples selected by using total sampling technique. This research administered a reading test consisting of 40 multiple-choice items in the pre-test and post-test. The mean score in pre-test was 60.15, while the mean score in post-test was 74.97. To determine the difference between pre-test and post-test, this research used t-test formula. After analyzing the data, it was found that the t-test score was 8.782, meaning that it was higher than t-table (2.034). From the result of data analysis, it was concluded that the Alternative Hypothesis (Ha) of this research was accepted. Thus, Listen-Read-Discuss (LRD) strategy significantly improved the reading comprehension of the second year students at SMK Dar El Hikmah Pekanbaru. Based on these findings, it was recommended that Listen-Read-Discuss (LRD) strategy was effective on improving the students’ reading comprehension, particularly in narrative text.